2011
DOI: 10.1080/09658211.2011.595723
|View full text |Cite
|
Sign up to set email alerts
|

Age-related positivity effects and autobiographical memory detail: Evidence from a past/future source memory task

Abstract: This study investigated whether the age-related positivity effect strengthens specific event details in autobiographical memory. Participants retrieved past events or imagined future events in response to neutral or emotional cue words. Older adults rated each kind of event more positively than younger adults, demonstrating an age-related positivity effect. We next administered a source memory test. Participants were given the same cue words and tried to retrieve the previously generated event and its source (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
78
3
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 58 publications
12
78
3
5
Order By: Relevance
“…One possibility is that these omissions were also due to deficits in retention: that is, at high mnemonic loads, older adults had deficits retaining all the information over time. Results compatible with this interpretation were obtained recently by Gallo, Korthauer, McDonough, Teshale, and Johnson (2011) who tested younger and older adults on a future imagining paradigm, and measured memory for both the details of each event and source memory (i.e. task condition), one day later.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…One possibility is that these omissions were also due to deficits in retention: that is, at high mnemonic loads, older adults had deficits retaining all the information over time. Results compatible with this interpretation were obtained recently by Gallo, Korthauer, McDonough, Teshale, and Johnson (2011) who tested younger and older adults on a future imagining paradigm, and measured memory for both the details of each event and source memory (i.e. task condition), one day later.…”
Section: Discussionsupporting
confidence: 57%
“…A second possibility is that older adults' poor metamemory abilities (Dunlosky & Connor, 1997;Shah & Craik, 1989) lead them to underestimate task demands and prevents them from exerting the necessary effort needed to perform well (see also Hertzog & Dunlosky, 2011). Gallo et al (2011) also found that subjective ratings of task performance were not related to source memory in older adults who completed a future imagining task, providing further evidence that such ratings in older adults may reflect other processes.…”
Section: Discussionmentioning
confidence: 86%
“…It appears that negative emotion may serve such behavioral adjustment in the case of past MTT, whereas it may be absent or highly reduced in future MTT. Consistent with this idea, recent findings suggest that positive future events are remembered with more detail than negative future events, whereas positive and negative past events are remembered with equal detail (Gallo et al, 2011). This does not mean that imagining a negative event in your personal future is always maladaptive.…”
supporting
confidence: 64%
“…Research from the past two decades has revealed that older adults tend to report more positive personal memories than their younger counterparts (e.g., Comblain, D'Argembeau, & Van der Linden, 2005;Dijkstra & Kaup, 2005;Gallo, Korthauer, McDonough, Teshale, & Johnson, 2011;Rubin & Schulkind, 1997;Singer, Rexhaj, & Baddeley, 2007). This pattern has been demonstrated in studies where participants are asked to retrieve events associated with verbal retrieval cues (Dijkstra & Kaup, 2005;Gallo et al, 2011;Rubin & Schulkind, 1997) and when participants are asked to retrieve important events from their pasts (Dijkstra & Kaup, 2005;Rubin & Schulkind, 1997;Singer et al, 2007).…”
mentioning
confidence: 87%